Phenotypic Detection of Metallo-?-lactamasesin Imipenem-resistant Bacteria at Hyderabad, Pakistan - A. A. PATOLI,; B. B. PATOLI,; S. JABEEN,; B. SHAIKH , (Sindh University Research Journal - SURJ (Science Series), 2020)
The current study was aimed to evaluate the occurrence and prevalence of metal based ?-lactamase producing Gramnegative bacterial pathogens from various clinical specimens. A total of eighty four (84)Gram-negative clinical isolatesfrom pus, blood, urine and peritoneal fluids were processed for the production of Metallo-?-Lactamases (MBL)using Combined Disk Diffusion Test.About 26.1% were found to produce metallo-?-lactamases. Among the various categories of clinicalspecimens the maximum percentage of MBL was produced by blood isolates (35%) followed by pus (30%) and urine (9%) isolates. Comparatively higher percentage (26.6%) of MBL producing isolates were recovered from the specimens of female patients than male (25.6%) patients. Odds Ratio [OR] was calculated to be 0.95 [CI (95%) = 0.36-2.52]. Statistically non-significant differences (p-value ? 0.05) for MBL productions were seen between the isolates recovered from male and female patients, suggesting MBL production to be an independent phenomenon of gender effect